Tinjauan Yuridis Faktor Pemicu Dan Pendekatan Intervensi Tawuran Remaja Di Bandar Lampung - Edo Arya Prabowo; Lucky Arijano Augusta Putra; Angga Alfiyan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research investigates the phenomenon of juvenile brawls with a focus on analyzing trigger factors and developing effective intervention approaches. Involving field research and psychological analysis, this research identifies that interpersonal conflict in the context of schools and urban communities plays a crucial role in triggering brawls. Factors such as economic strain, academic pressure, and lack of interpersonal understanding among teenagers stand out as major triggers. Apart from that, the influence of pop culture and the social environment also contributes significantly to the increase in brawl incidents. This research presents recommendations for developing preventive programs that involve collaboration between schools, families and communities. A holistic intervention approach, including psychological and social aspects, was identified as key to reducing and preventing youth brawls. It is hoped that this research can provide valuable insights for practitioners, researchers and policy makers in creating a safe and supportive environment for adolescent development.